(untitled) (Global Journal of Medical Research, 2023)
Objective To assess the feasibility and reproducibility of tubal anastomosis through a mini-laparotomy incision Design Descriptive case study Setting Academic medical center Patient s Sixteen patients with previous tubal sterilization who requested tubal re-anastomosis Intervention s Systematization of the operative steps for tubal re-anastomosis using a mini-laparotomy incision Main Outcome Measure s Primary outcome measures were feasibility and reproducibility secondary measures were tubal patency operative time complications and ergonomic qualities